An investigation into life needs across stages of recovery from aphasia : implications for service delivery - Alberts, Julia (Division of Communication Sciences and Disorders, 2017)
Recent shifts in the philosophy of aphasia rehabilitation have engendered research interests in the broad and long-term consequences of the condition. In response, this study aimed to describe and compare acute and long-term consequences of aphasia. Indepth interviews were conducted with fifteen adults at different stages of recovery poststroke. Topics probed included communication, family relationships, friendships, daily activities, independence, emotional status and self-image. Data was analysed thematically and meaningful units were coded and classified according to the International Classification of Functioning, Disability and Health (ICIDH-2). Results revealed common themes across the broad psychosocial consequences for individuals with aphasia and a concerning lack of public awareness of the aphasic condition. Further, a pattern of declining participation across the continuum of recovery was apparent. Drawing on the data obtained, the importance of long-term service delivery that focuses on the psychosocial adjustment of the individual with aphasia and their environment is highlighted.